Hidden Treasures of Petrinja – From Mystery to Attraction - Čanić, Marko; Krolo, Lea; Višnjak, Iva; Vukelić, Ana (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
This paper provides a comprehensive overview of the city of Petrinja, analysing its geographical location, historical development, demographic trends, economy and social and spatial changes caused by recent events, in particular the 2020 earthquake. The city is located in the Sisak-Moslavina County and is characterised by a favourable transport location, but also by challenges arising from the natural and social environment. The analysis of demographic indicators shows a continuous decline in population, negative natural growth, an ageing population and a strong out-migration, especially of the younger population. The structure of households, education and age structure are also analysed. The economic part of the paper focuses on the once strong industry, agriculture and attempts to develop tourism and crafts. After the earthquake, the economy was further weakened and many businesses and families have not yet recovered. Particular attention is paid to the consequences of the 2020 earthquake, which caused extensive material damage, displaced the population and further slowed down development. The paper concludes with a reflection on the future of the city – the need for better reconstruction, support for local initiatives, attracting investment and demographic renewal so that Petrinja can regain stability and realise its full potential.